PERAN KELUARGA DALAM PERKEMBANGAN SOSIAL EMOSIONAL ANAK USIA DINI: STUDI KASUS - Farina, Mahlida; Aslamiah; Novitawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The socio-emotional development of early childhood is strongly influenced by parenting patterns and internal family conditions. In today's social reality, more children are growing up in non-intact families with minimal paternal involvement and permissive parenting styles, which negatively affect their ability to build social relationships and manage emotions. This issue is crucial to examine, considering that early childhood serves as the foundation for subsequent psychosocial development. This study aims to explain the role of the family in the socio-emotional development of early childhood through a case study approach. The study employed a descriptive qualitative method, using observation, in-depth interviews, and documentation as data collection techniques. The findings reveal that: (1) the absence of a father figure leads to children being withdrawn and lacking self-confidence; (2) permissive parenting results in difficulties in emotional regulation; and (3) limited emotional support within the family contributes to low social skills in children.